Prevalence, course and associations of desire for hastened death in a UK palliative population: a cross-sectional study. Issue 2 (4th July 2011) - Price, Annabel; Lee, William; Goodwin, Laura; Rayner, Lauren; Humphreys, Rosemary; Hansford, Penny; Sykes, Nigel; Monroe, Barbara; Higginson, Irene; Hotopf, Matthew
Abstract : Objectives: To determine the prevalence, severity and remission of desire for hastened death (DHD) in a UK representative sample of patients with advanced disease receiving palliative care and to examine the associations of desire for death. Design: A cross-sectional survey with 4-week follow-up. Setting: St Christopher's Hospice, Sydenham, South London, which is a large hospice with homecare, outpatient and inpatient facilities serving five London boroughs. Participants: 300 patients newly referred to the hospice for palliative care. Main outcome measures: The Desire for Death Rating Scale (DDRS). Results: At T1 33/300 (11%) reported DHD and 11/300 (3.7%) had more serious or pervasive DHD. Of those who expressed DHD at T1 and were interviewed at both time points, 35% no longer reported these thoughts. Of those who reported no DHD at T1, 8% reported DHD at T2. The majority of those who had more severe DHD at T1 had a reduced DHD score by T2. Factors associated with T1 DHD included presence of non-malignant disease, depression, more severe physical symptoms, hopelessness and perceived loss of dignity. Conclusions: The prevalence of DHD was at the lower end of that seen in previous studies using similar samples. More severe DHD was uncommon and for most part remitted to some extent during the study. The provision of symptom control and timely detection and intervention for depression coupled with a focus on optimising function, instilling hope and preserving dignity are likely to contribute to alleviation of DHD in patients with advanced illness.